Evaluating the Impact of Problem Based Learning on Student's Metacognition in Science Learning: A Meta-Analysis Review - Dian Purnama Ilahi; Festiyed; Yerimadesi; Yulkifli; Lisa Utami; Arista Ratih (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to evaluate the impact of problem-based learning models on students' metacognition in science learning. This type of research is a meta-analysis using the PRISMA 2020 method. Articles from Scopus and Google Scholar databases were collected using Publish or Perish (PoP) software. From 8 articles that met the inclusion criteria, a total of 20 data were obtained to be processed in the meta-analysis. Data analysis was used with JASP software.The results of this metaanalysis research show that problem-based learning model provides moderate effectiveness on students' metacognition in science learning (r RE = 0.67; SE = 0.16; z = 4.24; p < 0.001). This shows that problem-based learning model can improve students' metacognition in science learning. Through PBL, students become more aware of their cognitive strategies and learn to organise them more effectively. Incorporating PBL into the science curriculum can significantly improve students' metacognition, leading to more independent and effective students. Therefore, widely adopting PBL in science education is recommended to achieve better learning outcomes